SIMULASI PENGATURAN OPERASI KERJA 3 POMPA DI BANDARA INTERNASIONAL JUWATA TARAKAN KALIMANTAN UTARA - Fajar Nugroho; RB Budi Kartika W; Suyatmo (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
Juwata Tarakan international airport has a clean water distribution facility to the terminal building area using three pump units that have the same specification. Clean water is distributed to toilets, mosques, shops and cafeterias. The water distribution control system is automated but not in accordance with the desired condition because the system works in serial if the previous pump is not working.In order to for the simulation design of the setting operation of three pumps to work properly it is necessary to do a favorable theory review, such as the theory that support. Some theories used to support the writing of this final task must be related and complement each other, including the theory of arduino as microcontroller board, sensor theory ACS712, DS18b20 sensor, relay, and others.The simulation design use to operation the three pumps works based on the time specified in each pump, with overcurrent and overheated protection on each pump to avoid potentially problematic pump (auto system), if the auto system becomes problem then the manual system can be operated .This simulation is used to describe the control system that is located in the juwata tarakan international airport of northern kalimantan